2018
DOI: 10.1016/j.jcma.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pandemic influenza A (H1N1) virus potential of catechin and gallic acid

Abstract: The present study demonstrates that catechin might be a safe reagent for long-term use to prevent influenza A (H1N1) virus infection; whereas gallic acid might be a sensitive reagent to inhibit influenza virus infection. We conclude that these two phyto-chemicals in TSL-1 are responsible for exerting anti-pandemic influenza A (H1N1) virus effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 24 publications
0
34
0
4
Order By: Relevance
“…Chlorogenic acid and gallic acid have also been demonstrated to suppress the in vitro and in vivo replication of influenza A virus, enterovirus 71 and hepatitis B and C viruses (Ding et al, 2017;Wang et al, 2009;You et al, 2018;Govea-Salas et al, 2016). Chlorogenic acid specifically inhibited the neuraminidase activity of influenza A viruses H1N1 and H3N2 that was the crucial mechanism of chlorogenic acid for blocking the release of progeny virions from infected cells (Ding et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid and gallic acid have also been demonstrated to suppress the in vitro and in vivo replication of influenza A virus, enterovirus 71 and hepatitis B and C viruses (Ding et al, 2017;Wang et al, 2009;You et al, 2018;Govea-Salas et al, 2016). Chlorogenic acid specifically inhibited the neuraminidase activity of influenza A viruses H1N1 and H3N2 that was the crucial mechanism of chlorogenic acid for blocking the release of progeny virions from infected cells (Ding et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[22]. GA has been reported to have antibacterial [23,24], antifungal [25], antioxidant [26], anticancer [27], antiinflammatory [28], antiviral [29] and antimutation properties [30]. Although several studies have revealed that GA exerts antimicrobial effects toward human pathogens, few studies have reported on the antimicrobial action against aquatic pathogens.…”
Section: Mechanisms Of Action Of Asgc and Ga Against V Harveyimentioning
confidence: 99%
“…Regarding the anti-viral role tea flavonoids have been shown to be strong agent [16]. Report demonstrates that catechin can prevent influenza A (H1N1) virus infection and gallic acid can inhibit influenza virus infection [17]. Last three decades several studies suggested that the regular consumption of green tea decreases influenza infection and some cold symptoms.…”
Section: Introductionmentioning
confidence: 99%